Importance of Financial Sectors in the Iranian Economy; An Analytical Appraisal of Shutting Down Effects of Financial Industries on Output and Employment - Gholamreza Keshavarz Haddad (فصلنامه پژوهش‌های اقتصادی ایران, 2005)
In this Paper financial services in the Iranian economy, which is portioned into 41 industries, is considered as a sector with a Leontief production function. Financial Sectors, buy inputs from other sectors, and provide services to expedite the cash fellows and risk transformation for other sectors. The former relations are called Backward Linkage and the later relations through which the sectors provide output to meet required cash fellow and risk reduction of economic activities are called Forward Linkage. In quantification of the linkages, employment and output elasticity, the forward index of value added, and backward linkage of final demand are used. Furthermore, direct and indirect effects of a hypothetical extraction of the sectors on output and employment are calculated. The results show that, although the linkages between financial sectors and the rest of the economic activities are not strong, their extraction will result in 225246.8 decrease in job opportunity, according to the 1370 input-output table produced by the Statistical Center of Iran.